2015
DOI: 10.14740/jocmr2171w
|View full text |Cite
|
Sign up to set email alerts
|

Positive Endocervical Margins at Conization: Repeat Conization or Colposcopic Follow-Up? A Retrospective Study

Abstract: BackgroundThe presence of residual cervical lesions was evaluated in patients submitted to repeat conization due to a finding of positive endocervical margins in a previous loop electrosurgical excision procedure (LEEP) specimen. In addition, the correlation between the presence of a residual lesion and risk factors for cervical cancer, and the use of repeat conization as first-choice treatment were analyzed.MethodsThis retrospective study included 44 patients submitted to repeat cervical conization or total h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
(15 reference statements)
2
5
0
Order By: Relevance
“…This finding demonstrates a high prevalence of residual disease if endocervical margin involvement was noted after conization. This result is similar to findings of other studies that reported persistence rates of approximately 45–55% in this situation [1, 4, 8]. In this study, menopausal status was strongly associated with a high risk of persistent disease: 81.2% in menopausal women versus 46.9% in nonmenopausal women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding demonstrates a high prevalence of residual disease if endocervical margin involvement was noted after conization. This result is similar to findings of other studies that reported persistence rates of approximately 45–55% in this situation [1, 4, 8]. In this study, menopausal status was strongly associated with a high risk of persistent disease: 81.2% in menopausal women versus 46.9% in nonmenopausal women.…”
Section: Discussionsupporting
confidence: 92%
“…It is estimated that the rate of recurrence two years after treatment in patients without compromised margins is approximately 4 to 18% with an average of 8% [3]. However, in patients with positive margins, this risk of recurrence is typically higher, and some studies report rates of approximately 52% [14].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, neither age nor glandular involvement were identified as risk factors for residual disease in patients with positive margins, which is similar to results in previously reported studies. [ 15 , 16 , 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Some assume that follow-up protocol is the ideal way for management of positive margin, [14] while others prefer a second surgical intervention such as repeat conization or hysterectomy. [3,11,[15][16][17] As for the management of positive margins, both over-treatment and insufficient treatment should be avoided. [18] Accordingly, many studies have focused on identifying the risk factors for residual and recurrent disease in patients with positive margin, such as age, menopausal status, TCT results, HPV infection, and the pathological characteristics of the conization specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation